The Anterior-Based Muscle-Sparing Approach to Total Hip Arthroplasty - Geller, Jeffrey A.; McGrory, Brian J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The minimally invasive, anterior-based muscle-sparing (ABMS) approach to total hip arthroplasty (THA) is utilized worldwide in select locations as an effective surgical technique. As the name suggests, it is completely muscle-sparing and touts the benefits of anterior-based surgery, including a lower dislocation rate, quicker return to baseline function, and lower narcotic use than many other surgical approaches. However, there is a paucity of collected information on the technique and research associated with this technique. This text serves as a compendium of information for those surgeons interested in utilizing this surgical approach as an all-inclusive reference. As an alternative anterior-based approach to the direct anterior surgical approach, some surgeons may find the technique an improved alternative for anterior hip-based surgery. Opening chapters present the history of the anterolateral approach and how to transition to the ABMS approach, including surgical anatomy. ABMS technique with the patient positioned in both the lateral and supine positions are then presented, including associated video segments. Considerations such as implant selection, fixation, and other tips and tricks are shared, along with comparisons to other approaches, patient-reported outcomes, complications and revision surgery techniques, and rehabilitation strategies. For hip surgeons looking to expand their armamentarium of surgical approaches, The Anterior-Based Muscle-Sparing Approach to Total Hip Arthroplasty is a terrific resource.
The idea of (3z(BMinimally Invasive Solution(3y (Btotal hip arthroplasty: History and perspective behind the modernization of surgery through the Watson-Jones muscle interval -- Transitioning to the ABMS Approach -- Surgical anatomy and approach -- The ABMS Total Hip Replacement, performed in the Lateral Position -- The ABMS Approach to Total Hip Replacement in the Supine Position -- Outpatient Total Hip Arthroplasty using an ABMS Approach -- Cementless ABMS Total hip replacement -- Cemented ABMS Total hip replacement -- Implant Selection in ABMS Total Hip Replacement surgery -- Tips & Tricks to Overcome the Learning Curve of the ABMS Approach to the Hip -- Surgical Navigation in the ABMS Approach to Total Hip Replacement -- Comparison of the ABMS Approach to Other Surgical Approaches for Total Hip Replacement -- Periprosthetic Joint Infection treatment through the ABMS -- How to Avoid Complication in the ABMS Total hip replacement -- Acetabular Revision THR using the ABMS approach -- Femoral Revision THR using the ABMS approach -- Total Hip Replacement for Fragility Fractures Using the ABMS in the Older Adult -- Outcomes of ABMS THA -- Rehabilitation after THR using the ABMS approach.s
Keywords: Orthopedics; Orthopaedics; Arthroplasty, Replacement, Hip